Multiracial graduate students’ lived experiences - MacDonald, Grizelda Lucille (Kansas State University, 2015)
The United States of America’s demographic population has shifted vastly to include a “new” multiracial growing population. Multiracial individuals are those who self-identify as two or more races, which now reflects a very young population. Higher education institutions are noticing an influx of more and more multiracial individuals, and many institutions are grappling with how to recognize and to support this growing population. Specifically, higher education institutions need to understand how multiracial graduate students think about their own racial identities and how they navigate their graduate school experiences. The purpose of this research was to gain a deeper understanding of multiracial graduate students’ lived experiences. There is an imperative to understand the daily experiences of multiracial graduate students to allow these students to retell the stories of their everyday lives in graduate school. The theoretical framework used to guide this study was critical race theory. Narrative inquiry methodology was the methodology chosen to focus on the unique voices and experiences of the participants in this study. Narrative analysis was employed to make meaning of the data retrieved from self-reflective writing samples and two semi-structured individual interviews with each of three participants. The findings from this research revealed the ever-present importance of racism and colorism and their impact on racial identity, the continued challenges of the campus climate experienced by multiracial students at a predominantly White institution (PWI), the impact and influence of religion at a PWI, and how multiracial students manage different types of relationships with peers and faculty. Implications for research and practice are provided as a result of the insights gleaned through this research about the lived experiences of three multiracial graduate students at one predominantly White higher education institution.
Keywords: Multiracial graduate students; Higher education; Multiracial theories; Multiracial college students; Critical race theory; Narrative inquiry; Higher Education (0745)